Creation of onomastic subcorpus and a few words about world experience - Rysbergen , Қ.Қ.; Rsaliyeva, Н.М.; Sadyrbayeva, З.Б.; Pashan, Д.М.; Seitbatkal, Ә.Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The Institute of Linguistics named after A. Baitursynov is developing an onomastic suвcorpus in the field of toponymy, which is an independent part of the National corpus. The paper discusses the directions and principles of construction of the onomastic suвcorpus. Thus, the main criteria for the design of the onomastic inner corpus are determined. The experience and features of the National corpus of the Kazakh language and some examples of big corpora in the world are described. The main purpose of the work is to determine the types of onomastic designations. Definition of toponyms in the corpus of English and Russian, transmission of linguistic and extralinguistic information, the frequency of occurrence of onomastic terms are determined. As a result of this analysis, comparisons and recommendations are made regarding the development of toponymic designations. As we have seen from the experience of foreign corpora, the more subcorpora, the more mature the National ccorpus. The emergence of onomastic subcorpus brings new opportunities for research by onomastic scholars. Because in the corpus you can quickly find texts where place names are found. This not only simplifies the search, but also contributes to a comprehensive study of onomastics. In addition, the printing of updated versions of onomastic dictionaries with the help of the subcorpus will be carried out quickly. The onomastic subcorpus is necessary not only in terms of approval and standardization of geographical names, but also in terms of systematization of toponyms, access to this national store for the purpose of their preservation and research and satisfaction of cognitive interests. The scientific-theoretical recommendations of the research paper contribute to the improvement of the definition of the onomastic corpus, as well as determine the role of the onomastic corpus in linguistic research. It is expected that the scope of the onomastic subcorpus, which began with the store of toponyms, will expand its scope with other types of onyms in the future.